This is Not Your Grandmother’s Faculty Development Program - Mack, Kelly M. (J Undergrad Neurosci Educ, 2018)
For decades, our nation has called upon higher education to create a more competitively-trained and diverse STEM workforce. While recent efforts to improve undergraduate STEM education have been successful, they have largely focused on “fixing” students and been devoid of the kind of effort needed to build institutional change capacity, moderate STEM departmental climate, and/or provide professional development for faculty. As a result, U. S. global preeminence in science and technology remains threatened, and the prevailing systems of oppression that continue to marginalize students from underrepresented groups remain intact. Redressing this particular trend calls not only for a deeper understanding of what works in STEM higher education reform, but also for an understanding of what works best for whom and under what conditions. To this end, my presentation for the 2017 FUN Workshop at Dominican University explored the most important advances in culturally responsive undergraduate STEM teaching, as well as the outcomes thereof. Attendees were invited to interrogate their own motivations for teaching and training future generations of diverse neuroscientists, and to contribute to developing both immediate and future next steps for national STEM higher education reform.